Rancang Bangun Robot Observasi Bawah Air - ROV (Remotely Operated Vihicle) Menggunakan Arduino UNO - Elva Susianti; Nanda Ardian Syahputra; Agus Urip Wibowo; Putut Son Maria (Jurnal Elektro dan Mesin Terapan, 2021)
Abstract This study describes the design of an underwater robot-Remotely Underwater Vehicle (ROV) which is controlled using a computer. The robot is controlled remotely using a GUI application built using VB. The microcontroller used as the processor is Arduino Uno R3 with a web camera as an eye to determine the next robot movement. This robot uses three motors as the driving force, and Bilge Pumps as the driving motor. The robot skeleton is made of acrylic by adding a float so that the robot can float on water. All electronic devices are controlled using cables. The robot can maneuver up to a depth of 2.25m, with the robot's response to movement commands, which is 61.935ms – 232.752 ms